Translating voices from the Tigris: The American Granddaughter as a case study - Hussein Hanoon Al-Sari, Falah ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
This study attempts to explore and analyze the image schemas in Kachachi’s translated novel, The American Granddaughter, and how they foster geopolitical worldviews by employing conceptual structures working as image schemas that establish specific mental models in collective audiences upon perception. Therefore, this study applies the cognitive linguistic approach to explore and investigate those image schemas. Along with image schemas, mental models are based on individuals’ embodied experiences and interaction with the physical world, be they kinesthetic or spatial. Therefore, image schemas represent an integral part of experience-based gestalt that governs the internal structure and formation of cognitive mental models. In other words, individuals draw upon image schemas as building blocks to the mental models they create about the world. The overlapping relationship between image schemas and mental models underpins the interrelationship between high-order cognitive processes and our encounter with everyday life experiences.